Who are the beneficiaries of the structural funds and the cohesion fund and how does the cohesion policy impact firm-level performance? - Bachtrögler, Julia (OECD Economics Department Working Papers, 2018)
This paper exploits a new database that is unique in its scale and scope containing detailed information on over two million projects carried out by one million firms that benefited from the European Regional Development Fund, the European Social Fund and the Cohesion Fund in 25 EU member countries during the multi-annual financial framework 2007-2013. This database is used to get a better understanding of the characteristics of the beneficiaries of European funds and to assess the impact of the European funds on the beneficiaries' performance in terms of employment growth, growth in fixed assets, and total factor productivity. While the data reveals substantial heterogeneity of beneficiaries and projects across and within countries, in terms of the number of projects, their total values, the average firm size and other aspects, some patterns are identified. The majority of co-funding goes to manufacturing firms as well as public institutions. The Cohesion Fund co-finances larger projects, carried out by larger, more capital-intensive firms that typically conduct large-scale infrastructure projects. In contrast, the European Social Fund co-finances smaller projects related to human capital and initiatives on the labour market. In terms of volume, the European Regional and Development Fund has the largest budget in total and co-finances a large variety of projects. Using propensity score matching techniques, we find mixed effects of structural and cohesion funds on the performance of a sample of manufacturing firms in six European countries. On average, firms that receive financial assistance hire more workers and increase their capital stock more. However, there is little evidence of additional positive total factor productivity effects for the beneficiaries